PERKEMBANGAN DESA TRANSMIGRAN SIPORA JAYA DI KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI (1987-2010) - Agustina, Ekawati; Hardi, Etmi; Yulia, Refni (Pendidikan Sejarah, 2014)
The arrival of the migrants in 1987 increased the number of residents in Sipora With the development of the residents, then Sipora Jaya village located in homesteader. For the problem formulated as follows: the process of formation and development of the Sipora Jaya Village from social, economic, and cultural. This research includes the study of history with research methods as follows : (1) heuristic, (2) internal and external criticism, (3) interpretation and (4) the stage of writing a thesis result. The results showed that the development of the village in Sipora Jaya village Sipora Utara District Kepulauan Mentawai Region (1987-2010), (1) Jaya Sipora Village have 3 village, there are Tunas Baru, Karang Anyar and Karya Bakti.. The total area of Sipora Jaya Village approximately 40.113 ha, (2) Population at Sipora Jaya village are migrants from Java coupled with native Mentawai. The level of education in the village of Sipora Jaya village also began to increase in line with the development of the village and community income. Social and cultural developments seen from the adjustment to the resident or fellow participants transmigration program. The cooperation between the population are of mutual aid in the cleaning of the streets and roads are often grassy often hollow. Population fo Sipora Jaya village hardly ever any physical conflict that occurred only non-physical conflicts that occur as a difference of opinion that occur in a consultation conducted . Tolerance between the Mentawai and Java tolerance that occurs is between faiths in daily life and also celebrate the big day in their respective religions. Economic life of the people in the village Transmigrants Sipora Jaya village, education, housing, and decent work. Transmigrants given community service provision areas of land for residential and agricultural land. Government gives ease and accelerate the dependence of the migrants in an effort to improve their lives through the provision of life assurance Keyword: development, village, transmigration